2010
DOI: 10.1158/0008-5472.can-09-1462
|View full text |Cite|
|
Sign up to set email alerts
|

α2-Macroglobulin Inhibits the Malignant Properties of Astrocytoma Cells by Impeding β-Catenin Signaling

Abstract: Targets that could improve the treatment of brain tumors remain important to define. This study of a transformation-associated isoform of α2-macroglobulin (A2M*) and its interaction with the low-density lipoprotein receptor-related protein-1 (LRP1) suggests a new mechanism for abrogating the malignant potential of astrocytoma cells. LRP1 bound A2M* found to be associated with an inhibition of tumor cell proliferation, migration, invasion, spheroid formation, and anchorage-independent growth. Transcriptional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 46 publications
(40 reference statements)
0
45
0
2
Order By: Relevance
“…Amongst these, adherens junctions connect intercellular adhesion to the actin cytoskeleton and thus are crucial not only during morphogenesis of epithelial tissues but also in tissue homeostasis. The adhesive backbone of adherens junctions is formed by cadherins [12], calcium-dependent transmembrane glycoproteins, which via binding to catenins like b-catenin, a-catenin and/or p120-catenin are linked to and interact with the cytoskeleton and also play important roles in cell polarity and signaling [13,14]. In healthy liver, it was shown that E-cadherin is expressed in periportal but not in perivenous hepatocytes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst these, adherens junctions connect intercellular adhesion to the actin cytoskeleton and thus are crucial not only during morphogenesis of epithelial tissues but also in tissue homeostasis. The adhesive backbone of adherens junctions is formed by cadherins [12], calcium-dependent transmembrane glycoproteins, which via binding to catenins like b-catenin, a-catenin and/or p120-catenin are linked to and interact with the cytoskeleton and also play important roles in cell polarity and signaling [13,14]. In healthy liver, it was shown that E-cadherin is expressed in periportal but not in perivenous hepatocytes [15].…”
Section: Introductionmentioning
confidence: 99%
“…[17]’[23] As a protease inhibitor, it is reported to inhibit tumor cell proliferation when binding to low-density lipoprotein receptor-related protein 1 (LRP 1). [24] The N-glycosylation of A2MG has been chosen as an initial system to demonstrate our method for the study of fucosylation ratios since it is a relatively high abundance protein with eight potential fucosylation sites and is efficiently purified with an available commercial antibody. In this study, we utilized a label-free LC-MS/MS method to monitor changes of human A2MG core-fucosylation at specific glycosylation sites based on precursor ion intensities of Endo F3 treated glycopeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Many cancer-related genes were found closest to LCN2. For example, interaction of A2M (alpha2-macroglobulin) with low-density lipoprotein receptor-related protein-1 (LRP1) is associated with an inhibition of tumor cell proliferation, migration, invasion, spheroid formation, and anchorage-independent growth through inhibition of beta-catenin signaling in astrocytoma cells37. DCN (also called decorin) is known to interfere with cellular events of tumorigenesis mainly by blocking various receptor tyrosine kinases (RTK) such as the EGFR, Met, IGF-IR, PDGFR and VEGFR2.…”
Section: Disscussionmentioning
confidence: 99%